A controlled anion exchange strategy to synthesize Bi2S3 nanoparticles/plate-like Bi2WO6 heterostructures with enhanced visible light photocatalytic activities for Rhodamine B. Issue 2 (1st February 2016) - Li, Xiaoguang; Li, Yinle; Shen, Jianfeng; Ye, Mingxin
Abstract: Bi2 S3 /Bi2 WO6 semiconductor heterostructures with enhanced visible light photocatalytic activity were firstly prepared through a facile in-situ anion exchange approach at relatively low temperature, using thioacetamide as sulphur source and Bi2 WO6 nanosheets as precursors. Bi2 S3 nanoparticles decorated on the surface of 2D plate-like Bi2 WO6 nanosheets were analyzed by using X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy etc. Photocatalytic experiments indicate that such Bi2 S3 /Bi2 WO6 composites possess higher photocatalytic activity for the degradation of Rhodamine B under visible light irradiation in comparison with pure Bi2 S3 or Bi2 WO6 . Among Bi2 S3 /Bi2 WO6 composites with different contents of Bi2 S3, the Bi2 S3 /Bi2 WO6 composite with 30% Bi2 S3 exhibits the highest photocatalytic efficiency. Based on the calculated energy band positions and photoluminescence spectrum, it was postulated that enhanced photocatalytic property could be ascribed to the reduction of the recombination rate of photogenerated electron–hole pairs and the heterojunction interface. Moreover, these results suggest that the heterostructured photocatalysts can be potentially applied in environmental protection and waste water treatment.